Social Dynamics and Community Identity Change Among the Residents Around UIN Sunan Ampel Surabaya - Rizka Dwi Nurhana; Aditya Hermansyah (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
The State Islamic University of Sunan Ampel Surabaya (UINSA), previously known as the State Institute of Islamic Studies (IAIN) Sunan Ampel, has undergone significant changes since its establishment in 1965, culminating in its transformation into UINSA in 2013. UINSA introduced the